2022
DOI: 10.3389/fpubh.2022.950859
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of global research trends on post-stroke pneumonia: Current development status and research Frontiers

Abstract: BackgroundAs one of the most common complications of stroke, post-stroke pneumonia significantly increases the incidence of adverse outcomes, mortality, and healthcare costs for patients with stroke. As the field of post-stroke pneumonia has gained interest in the recent years, there has been an increasing number of publications on post-stroke pneumonia research worldwide. Therefore, a more comprehensive understanding of the field is needed now. This paper is intended to analyze the research status and detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…Co-citation refers to two or more documents being cited by one or more articles at the same time. Highly cited information is generally high-quality research in a field that has had a significant impact on innovation and discovery ( 9 ). A survey of author information revealed that all of the top 10 active authors published at least 17 articles.…”
Section: Discussionmentioning
confidence: 99%
“…Co-citation refers to two or more documents being cited by one or more articles at the same time. Highly cited information is generally high-quality research in a field that has had a significant impact on innovation and discovery ( 9 ). A survey of author information revealed that all of the top 10 active authors published at least 17 articles.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the world's smart healthcare devices are produced in the US, and the application of smart healthcare in the US elderly population is relatively mature [21]. In addition to the total number of citations, the average number of citations per article is an important indicator of the quality of a publication [22]. Our results show that the ranking of average citations per item is not the same as that based on the number of publications.…”
Section: Discussionmentioning
confidence: 74%
“…High citation counts are typically associated with high-quality research that exerts a significant influence on innovation and discovery within a field; generally, the more citations a study receives, the greater its impact 31 . Our analysis revealed that the top 10 authors by publication volume were all from China, aligning with the country’s prominent role in the national publication statistics.…”
Section: Discussionmentioning
confidence: 99%